2014
DOI: 10.1513/annalsats.201405-203as
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Management of Lung Infections in Cystic Fibrosis. II. Nontuberculous Mycobacteria, Anaerobic Bacteria, and Fungi

Abstract: Airway infections are a key component of cystic fibrosis (CF) lung disease. Whereas the approach to common pathogens such as Pseudomonas aeruginosa is guided by a significant body of evidence, other infections often pose a considerable challenge to treating physicians. In Part I of this series on the antibiotic management of difficult lung infections, we discussed bacterial organisms including methicillin-resistant Staphylococcus aureus, gram-negative bacterial infections, and treatment of multiple bacterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 88 publications
1
75
0
1
Order By: Relevance
“…Acute ABPA flares can be treated with intravenously administered pulsed methylprednisolone at 10-15 mg/kg/day for a three day period every month. 30,45 Methylprednisolone was administered to four CF-ABPA patients in this study and a trend towards reduction in Af-stimulated CD203c values was observed after treatment. However, this trend was not significant (P = 0.1604) warranting future longitudinal study with increased numbers to examine the effect of corticosteroid treatment on Af sensitization and potentially the use of the BAT to monitor treatment responses.…”
Section: Discussionmentioning
confidence: 77%
“…Acute ABPA flares can be treated with intravenously administered pulsed methylprednisolone at 10-15 mg/kg/day for a three day period every month. 30,45 Methylprednisolone was administered to four CF-ABPA patients in this study and a trend towards reduction in Af-stimulated CD203c values was observed after treatment. However, this trend was not significant (P = 0.1604) warranting future longitudinal study with increased numbers to examine the effect of corticosteroid treatment on Af sensitization and potentially the use of the BAT to monitor treatment responses.…”
Section: Discussionmentioning
confidence: 77%
“…It was previously believed that NTM pulmonary infection developed exclusively in individuals following environmental acquisition, as mycobacteria, is ubiquitous in soil and water [28]. However, an outbreak of M. abscesses ssp massielense was first documented at a CF clinic in Seattle, Washington, involving five patients.…”
Section: Ntm Epidemiologymentioning
confidence: 99%
“…The results of the present study and other researches prove that fungi, particularly A. fumigatus species are a potential pathogen of severe invasive respiratory infections in CF patients [39]. Therefore, an efficient antifungal therapy in CF patients has to be preceded with mycological examination in order to determine etiology of infection and drug-sensitivity of the pathogen to antibiotics.…”
Section: Discussionmentioning
confidence: 57%